Wheat germ oil vitamin E cytoprotective effect and its nutrigenomics signature in human hepatocyte lipotoxicity. Issue 9 (September 2022) - Bartolini, Desirée; Marinelli, Rita; Stabile, Anna Maria; Frammartino, Tiziana; Guerrini, Angela; Garetto, Stefano; Lucci, Jacopo; Migni, Anna; Zatini, Linda; Marcantonini, Giada; Rende, Mario; Galli, Francesco
Abstract: Wheat germ oil (WGO) is rich in α-tocopherol (vitamin E, VE), a vitamin that has long been suggested to exert hepatoprotective effects. In this study, this function of WGO-VE and its transcriptomics fingerprint were investigated in comparison with RRR−α-tocopherol and all-rac- α-tocopherol (nVE and sVE, respectively), in human liver cells treated with oleic acid (OA) to develop steatosis and lipotoxicity. Used in chemoprevention mode, all the VE formulations afforded significant reduction of the OA-induced steatosis and its consequent impact on lipotoxicity indicators, including ROS production and efflux (as H2 O2 ), and apoptotic and necrotic cell death. A trend toward a better control of lipotoxicity was observed for WGO-VE and nVE compared to sVE. Gene microarray data demonstrated that these effects of VE formulations were associated with significantly different responses of the cellular transcriptome to compensate for the modifications of OA treatment, including the downregulation of cellular homeostasis genes and the induction of genes associated with defects of liver cell metabolism, fibrosis and inflammation, liver disease and cancer. Ingenuity Pathway Analysis data showed that WGO-VE modulated genes associated with liver carcinogenesis and steatosis, whereas nVE modulated genes involved in liver cell metabolism and viability biofunctions; sVE did not significantly modulate any gene dataset relevant to such biofunctions. In conclusion, WGO-VE prevents lipotoxicity in human liver cells modulating genes that differ from those affected by the natural or synthetic forms of pure VE. These differences can be captured by precision nutrition tools, reflecting the molecular complexity of this VE-rich extract and its potential in preventing specific cues of hepatocellular lipotoxicity. Abstract : Vitamin E; Alpha-tocopherol; Wheat germ oil; Lipotoxicity; NAFLD; NASH; Transcriptomics; Liver; Nutrigenomics; Human hepatocytes; Reactive oxygen species; Precision nutrition.